P88 The evaluation of Exophiala in paediatric cystic fibrosis. (12th November 2015) - Patel, LB; Panickar, J; Shawcross, A; Wilkinson, S
Abstract : Introduction: The increasing prevalence of fungal pathogens in paediatric cystic fibrosis (CF) is challenging current practice. Whilst respiratory growth and colonisation with Exophiala, a saprophytic fungus is documented; the susceptibility, clinical manifestation and management is unclear. Aim: To evaluate the clinical manifestation of Exophiala and the role of antifungal therapies in paediatric CF. Setting: Royal Manchester Children's Hospital provides tertiary care for 182 patients and shared care for 170 patients encompassing a diverse range of genotypes. Population: Fifteen patients have yielded Exophiala positive sputum swabs on routine screening over 24 months. Measures: Objective measures of disease severity and demographics; age, gender, BMI (Z-score), lung function, hospital admissions are assessed against Exophiala growth and co-existing pathogens. Antifungal treatment regimens are described and compared. Analysis: Significant clinical manifestation of Exophiala and evidence of eradiation in this population is described. Results: Data reveals no significant difference in sex ratio 8:7 (♂:♀) though distribution is skewed towards older patients 46.7% (n = 7) >15 years, 26.6% 12–14 years, 12.5% 10 years, 12.5% 5–7 years. Two distinct categories of carriage are evident; sporadic growth (n = 9) and colonisation (n = 6). All positive sputa contained ≥2 organisms' suggesting coexisting colonisation. 73.3% of all patients and 100% percent of patients colonising Exophiala had coexisting colonisation of Candida albicans . 100% of patients colonising Exophiala also had a drop in BMI and Z-score from diagnosis to date of study. They also had a rate of >9 admissions/year. Lung function tests revealed variation independent of carriage. Symptomatic carriage of Exophiala was treated with triazoles; voriconazole, itraconazole and posaconazole though 50% of blood triazole levels were below therapeutic range. One patient cleared Exophiala without antifungal treatment. No further growth was noted following itraconazole treatment on initial growth in another patient. Colonisation was treated successfully with intravenous voriconazole, though re-colonised 4 months later. Colonisation was evident in 2 patients despite 6–12 months of oral voriconazole but was eradicated on switching to oral posaconazole. Conclusion: Data from this single centre study suggests that some paediatric CF patients may be more susceptible to fungal infections. Exophiala carriage manifestation varies and may affect height and weight. Exophiala eradication can be achieved.